Chronic remote ischaemic conditioning in patients with symptomatic intracranial atherosclerotic stenosis (the RICA trial): a multicentre, randomised, double-blind sham-controlled trial in China. Issue 12 (December 2022) - Hou, Chengbei; Lan, Jing; Lin, Yinan; Song, Haiqing; Wang, Yuan; Zhao, Wenbo; Li, Sijie; Meng, Ran; Hao, Junwei; Ding, Yuchuan; Chimowitz, Marc I; Fisher, Marc; et al.
Summary: Background: Intracranial atherosclerotic stenosis (ICAS) is one of the most common causes of stroke worldwide, and it is associated with a high risk of recurrent stroke with currently recommended treatments. We aimed to evaluate the effect of chronic remote ischaemic conditioning on prevention of ischaemic events in patients with symptomatic ICAS. Methods: The RICA trial is a multicentre, randomised, double-blind, sham-controlled trial at 84 stroke centres in China. Patients aged 40–80 years with ischaemic stroke or transient ischaemic attack attributable to angiographically verified 50–99% stenosis of a major intracranial artery were randomly assigned (1:1), via an interactive web-based system by computer-generated randomisation code, to either remote ischaemic conditioning or sham remote ischaemic conditioning once daily for 12 months and voluntarily thereafter. All investigators and patients were masked to treatment allocation. The primary efficacy endpoint was the time to first occurrence of non-fatal or fatal ischaemic stroke, with survival analysed by the Kaplan-Meier method. Primary and safety analyses were done in the intention-to-treat population. The RICA trial is registered with ClinicalTrials.gov, number NCT02534545. Findings: Between Oct 28, 2015, and Feb 28, 2019, 3033 patients were enrolled and randomly assigned to either remote ischaemic conditioning (n=1517; intervention group) or sham remote ischaemic conditioning (n=1516; sham group). Median follow-up was 3·5 years (IQR 2·7–4·4). A non-fatal or fatal ischaemic stroke occurred in 257 (16·9%) patients in the intervention group compared with 288 (19·0%) patients in sham group. There was no difference in the survival distribution for time to first occurrence of non-fatal or fatal ischaemic stroke (hazard ratio 0·87, 95% CI 0·74–1·03; p=0·12). In the intervention group, 79 (5·2%) patients died from any cause, and in the sham group, 84 (5·5%) patients died from any cause (hazard ratio 0·93, 95% CI 0·68–1·27; p=0·65). No intervention-related serious adverse events were observed. Interpretation: No evidence was found for a difference between remote ischaemic conditioning and sham remote ischaemic conditioning in lowering the risk of ischaemic stroke in patients with symptomatic ICAS. The benefit of remote ischaemic conditioning might have been diluted by poor compliance. Future studies of remote ischaemic conditioning in this population should address challenges in patients' compliance and assess longer term treatment. Funding: Ministry of Science and Technology China, Beijing Municipal Education Commission, Beijing Municipal Finance Bureau. Translation: For the Chinese translation of the abstract see Supplementary Materials section.